Isolated Gallbladder Ascariasis Causing Acalculous Hydrops: Management of a Rare Surgical Entity - Muhammad Arisma Dwirian Putra; Ahmad Fakhrozi Helmi; Ali Hanafiah; Alsen Arlan (Sriwijaya Journal of Surgery, 2026)
Introduction: Ascariasis, caused by the nematode Ascaris lumbricoides, affects approximately one billion people globally. While hepatobiliary involvement is a recognized complication, isolated gallbladder ascariasis is exceptionally rare, accounting for less than 2.1% of biliary cases due to the anatomical resistance provided by the tortuous valves of Heister. This condition presents a significant diagnostic dilemma, often mimicking acute acalculous cholecystitis, and carries a high risk of complications if mismanaged. Case presentation: We report the case of a 57-year-old female presenting with acute-on-chronic right upper quadrant pain. Physical examination revealed localized tenderness without jaundice. Laboratory investigations demonstrated leukocytosis (15,460/mm³), significant eosinophilia (8%; absolute count 1,236/mm³), and cholestasis with elevated Alkaline Phosphatase (133 U/L). Ultrasonography, the diagnostic gold standard, revealed a distended gallbladder consistent with hydrops and a mobile, tubular echogenic structure—the inner tube sign—extending into the cystic duct. The patient underwent an open cholecystectomy. Intraoperatively, a critical retrograde milking maneuver was performed to dislodge the worm from the cystic duct back into the gallbladder to prevent transection. The Common Bile Duct was palpated and confirmed to be free of stones or parasites. A viable Ascaris worm was extracted from the specimen. Conclusion: Isolated gallbladder ascariasis must be considered in the differential diagnosis of acalculous biliary disease in endemic regions. Ultrasonography is superior to other modalities for diagnosis. Surgical intervention is mandatory when hydrops or cystic duct impaction occurs, with meticulous attention to cystic duct clearance to prevent biliary sequelae. The patient was discharged on postoperative day 3 without complications.